Exploring and Establishing a Framework For Effective Governance in European Grassroots Sports Organisations - Mark Lowther; Simone Digennaro; Antonio Borgogni; Angela Parry Lowther (Journal of Applied Sports Management, 2016)
This paper is based on a study that was initiated to better understand the dynamics of the grassroots sport landscape and establish a framework for effective governance practice in this important area of sport policy and management. Researchers had previously identified the value of exploring good governance specific to the nonprofit sector and in particular the unique features of informal sports organisations and small community clubs. The research methodology blended a meta-analysis of relevant literature to identify key principles followed by primary data collection to evaluate and validate the emerging framework. The main results of the study provided a typology of the sport governance landscape and clear evidence of the need to develop a framework for effective governance appropriate to the needs of grassroots sports organisations. Furthermore, it supported the construction of a flexible and dynamic self-regulatory instrument—known as SATSport—that organisations might use for measuring and illustrating commitment to good governance.
Keywords: governance; grassroots sport; good practice; self-assessment